Fluralaner injectable suspension (Bravecto® injectable) for dogs remains effective against Ixodes ricinus infestations for one-year - Georg von Samson-Himmelstjerna; Christina S. Helm; Jürgen Krücken; Eva Zschiesche; Lea Heinau; Ard M. Nijhof; Ivo Petersen (Parasites & Vectors)
Abstract Background Tick-borne pathogens are emerging in many regions worldwide with seasonal transmission often shifting to year-round transmission in temperate climatic zones due to climate change. This situation makes year-round protection against ticks advisable. The objective of the study was to confirm the efficacy of a single injection of fluralaner against Ixodes ricinus ticks for up to 56 weeks. Methods The study was a single-site, blinded, negative controlled, randomized efficacy study conducted with 20 female dogs. Dogs were randomized into two groups based on tick counts at pre-infestation. Dogs were infested with approximately 45 I. ricinus female ticks plus 5 male ticks at 17 time points over a year. Bravecto® injectable (15 mg fluralaner /kg BW) as Investigational Veterinary Product (IVP) was administered once as a subcutaneous injection 48 h after the first experimental infestation. Female ticks were counted at 48 ± 4 h post-treatment or post-infestation to evaluate immediate and persistent efficacy, respectively. Results The tick infestation per infestation day recorded from individual dogs in the negative control group ranged from 0 to 58. At each counting time point, at least seven dogs in the negative control group were infested with ≥ 25% of the ticks placed on them, indicating an adequate tick infestation and a sufficient tick challenge at each time point. The IVP was well tolerated in all dogs. Significantly fewer (p < 0.0001) live attached ticks were recorded from the IVP treated group compared to the control group at each time point. Based on arithmetic means of live attached tick counts, the IVP was 94.97% effective 7 days after administration. Persistent efficacy over one year following IVP administration was confirmed. The treatment efficacy after 12 and 13 months was 99.16% and 96.22%, respectively. Conclusions Based on the significant reduction in mean live attached I. ricinus counts compared to the negative control group, efficacy based on arithmetic mean ≥ 90%, and adequacy of infestation in the control dogs, the IVP was effective against existing and new I. ricinus tick infestations for up to 394 days following administration. Graphical Abstract